2022
DOI: 10.1002/anie.202200725
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized [2+2]‐Cycloadditions of Alkenylboronates and Alkenes

Abstract: A new strategy for the synthesis of highly versatile cyclobutylboronates via the photosensitized [2 +2]-cycloaddition of alkenylboronates and alkenes is presented. The process is mechanistically different from other processes in that energy transfer occurs with the alkenylboronate as opposed to the other alkene. This strategy allows for the synthesis of an array of diverse cyclobutylboronates. The conversion of these adducts to other compounds as well as their utility in the synthesis of melicodenine C is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 87 publications
2
45
0
Order By: Relevance
“…While several strategies are known for cyclobutylboronate synthesis, [2 + 2]-cycloadditions retain their own importance because (1) the reactions are convergent, (2) the alkene starting materials are generally widely available, and (3) products can be prepared that would be inaccessible by other approaches. , With respect to photochemical [2 + 2]-cycloaddition, , prior work has demonstrated that alkene triplet excited states can be captured with alkenylboronates. More recently, our lab has demonstrated that alkenylboronates can be photosensitized and undergo reaction with a variety of activated alkenes (e.g., styrenes, dienes) . In the latter case, the Bpin unit acted as an activating group to allow for the cycloaddition to proceed in good yield.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While several strategies are known for cyclobutylboronate synthesis, [2 + 2]-cycloadditions retain their own importance because (1) the reactions are convergent, (2) the alkene starting materials are generally widely available, and (3) products can be prepared that would be inaccessible by other approaches. , With respect to photochemical [2 + 2]-cycloaddition, , prior work has demonstrated that alkene triplet excited states can be captured with alkenylboronates. More recently, our lab has demonstrated that alkenylboronates can be photosensitized and undergo reaction with a variety of activated alkenes (e.g., styrenes, dienes) . In the latter case, the Bpin unit acted as an activating group to allow for the cycloaddition to proceed in good yield.…”
mentioning
confidence: 99%
“…The initial reaction optimization was conducted with allyl alcohol ( 1 ) and E -styrenylBpin ( 2 ). The choice to use E -styrenylBpin ( 2 ) stems from the fact that the sytrenyl component could be sensitized with common visible-light-activated sensitizers, , thus avoiding the use of high-energy UV light at this stage of development. Treatment of allyl alcohol ( 1 ) and E -styrenylBpin ( 2 ) in the presence of fac- Ir­(ppy) 3 did not lead to product formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The [2+2]-cycloaddition of alkyl boronate ester 2 with 4-methoxy styrene under photochemical irradiation of 456 nm blue LED with fac-Ir(ppy)3 as a photosensitizer and subsequent oxidation with NaBO3‧4H2O lead to cyclobutanol derivative 34 in 67% yields and 4:1 diastereomeric ratio. 64 To further demonstrate the synthetic utility, the developed methodology was employed to devise the synthesis of several bioactive compounds. We have also utilized vinyl boronate ester 18 to synthesize stilbene derivatives 35-37.…”
Section: Scope Of Manganese Catalyzed Acceptorless Dehydrogenative Bo...mentioning
confidence: 99%
“…It is pertinent to note this allowed a series of boron functionalities of different hybridisation states to be compatible with model reaction conditions. Recently Brown and co‐workers provided a striking example demonstrating EnT‐catalysed intermolecular [2+2] cycloaddition of alkenyl boronic esters (Scheme 18, bottom) [103] . Mechanistic studies identified a triplet energy transfer mechanism highlighting that energy is transferred to the alkenyl (styrene or diene) organoboron species.…”
Section: Photochemical Strategies Retaining the C−b Bondmentioning
confidence: 99%